Analisis Gabungan Sisa Hasil Usaha Koperasi Di Provinsi Jawa Timur Periode 2012-2021 - Siti Alifah Handayani; Nazwa Fazirah Nasution; Muhammad Bagas Ardhana; Dodi Jese Rianto Siburian; Henny Mawarta Siregar; Sasmi Ebigael Sinaga (Transformasi: Journal of Economics and Business Management, 2023)
In Indonesia, there must be a business entity that plays a role in creating an advanced, just and prosperous society, which prioritizes mutual welfare, and a form of business called a cooperative. One of the cooperative performance indicators that is important to analyze is the remaining results of operations, which can be used as a source of income for the cooperative and its members. Through this analysis, it is hoped that detailed and comprehensive information can be obtained regarding the performance of cooperatives in the province of East Java, especially in terms of remaining operating results. This information can be used as a reference for cooperatives and the government in formulating more appropriate strategies and policies in developing cooperatives in the region, as well as encouraging more inclusive and sustainable economic growth. In the economic structure of this province, there are two types of cooperatives that play an important role, namely sharia cooperatives and conventional cooperatives. One of the provinces in Indonesia that has a large number of cooperatives is East Java. Such as consumer cooperatives, savings and loan cooperatives, agricultural cooperatives, farmer cooperatives, fishing cooperatives, credit cooperatives, producer cooperatives, and a large number of other types of cooperatives are among the many types of cooperatives. In East Java, there are various cooperatives that have succeeded in increasing the welfare of members through good and efficient business management. Apart from own capital, there is also capital from outside the cooperative which affects the SHU level in East Java Province.